2009
DOI: 10.1086/599347
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Placental Transportation of Maternal Antibodies Specific forNeisseria meningitidisSerogroup C,Haemophilus influenzaeType B, Diphtheria, Tetanus, and Pertussis

Abstract: ISRCTN14204141 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
46
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 36 publications
11
46
1
2
Order By: Relevance
“…The level of MenC PS-specific antibodies detected in the present study is very similar to the concentration of 0.23 g/ml that we found previously in cord blood samples in another study from the same period (5). The findings of the present study support the idea that antibodies in children decline rapidly after birth and that transferred maternal antibodies do not protect children during their entire first year of life.…”
supporting
confidence: 90%
“…The level of MenC PS-specific antibodies detected in the present study is very similar to the concentration of 0.23 g/ml that we found previously in cord blood samples in another study from the same period (5). The findings of the present study support the idea that antibodies in children decline rapidly after birth and that transferred maternal antibodies do not protect children during their entire first year of life.…”
supporting
confidence: 90%
“…The antibody levels of umbilical cord blood are similar or higher than those of the mother (21)(22)(23). To investigate maternal seroprevalence, there are no issues related to using umbilical cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…Although no clinical data on the effectiveness and tolerability of maternal immunization are yet available, several studies have reported that placental transfer of antibodies against pertussis may be effective. 40,41 Currently, 2 registered clinical trials have begun recruiting participants for testing maternal immunization with acellular pertussis vaccines. 68 Decreasing the effectiveness of maternal antibodies from 89% to 70% resulted in a slight increase in the ICER (from €3500 [$4900]/QALY to €3600 [$5000]/ QALY).…”
Section: Discussionmentioning
confidence: 99%
“…22 The unborn child was assumed to acquire protective maternal antibodies and, therefore, may be protected immediately after birth, both by the antibodies and as a consequence of reduced risk of transmission from the mother. [36][37][38][39][40][41][42] Protection provided by maternally acquired antibodies in infants was assumed to last 4 months, 43 which bridged the gap to where protection was assumed from the immunization program already in place. Furthermore, it was assumed that, because of the rapid decrease in antibody titers after 6 to 12 months, the vaccination only protected the infant of the current pregnancy.…”
Section: Methodsmentioning
confidence: 99%